Agricultural services development project - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The subproject is intended to increase farm family incomes, particularly in the Southeastern Islands, by addressing identificable constraints to agricultural production and development, achieve a higher degree of self-sufficiency in agricultural production and earn foreign exhange throughlarge-scale production of export-oriented crops.